Research Study on Impact Assessment of Accelerated Irrigation Benefit Programme Final Report Annexure-B - Planning Commission (Planning Commission, 2002)
There are 2 Irrigation projects (major/medium/ ERM) in the state of Goa under AIBP scheme namely: Salauli Irrigation Project -Major and Tillary Irrigation Project (a joint venture of Govt, of Goa and Govt, of Maharashtra) - Major These two projects were included under AIBP scheme in the year 1997-98 and 2000-2001 respectively.
Planning Commission Government of India
Planning Commission Government of India